2015
DOI: 10.1002/jsfa.7171
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of α‐terpineol production by limonene biotransformation using Penicillium digitatumDSM 62840

Abstract: Among these three strains tested, P. digitatum DSM 62840 was proved to be an efficient biocatalyst to transform (R)-(+)-limonene to α-terpineol. Further studies revealed that the optimal growth phase for biotransformation was in the medium log phase of this strain. The biotransformation represented a wide tolerance of temperature; α-terpineol concentration underwent no significant change at 8-32 °C. The biotransformation could also be performed using resting cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…The researches on the biotransformation of limonene have been reported for decades, including the isolation of microorganisms (Rottava et al, 2010a,b;Badee et al, 2011;Bier et al, 2017), the optimization of bio-transformation process (Bicas et al, 2008;Bicas et al, 2010;Molina et al, 2019) and the factors affecting the biotransformation (Prieto et al, 2011;Tai et al, 2016). Nevertheless, industrial applications of the limonene bioconversion are still limited because of the substrate inhibition in the liquid medium and the difficulty of the product isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researches on the biotransformation of limonene have been reported for decades, including the isolation of microorganisms (Rottava et al, 2010a,b;Badee et al, 2011;Bier et al, 2017), the optimization of bio-transformation process (Bicas et al, 2008;Bicas et al, 2010;Molina et al, 2019) and the factors affecting the biotransformation (Prieto et al, 2011;Tai et al, 2016). Nevertheless, industrial applications of the limonene bioconversion are still limited because of the substrate inhibition in the liquid medium and the difficulty of the product isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium digitatum is a major fungal pathogen of citrus fruits, and it is reported that this fungal had the potential application in detoxifying monoterpenes (Molina et al, 2013). In our previous study, it is observed that P. digitatum strain DSM 62840 could convert limonene into α-terpineol with high regioselectivity (Tai et al, 2016). And the differentially expressed proteins at different periods of limonene biotransformation were explored using the isobaric tag for relative and absolute quantitation (iTRAQ) (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cosolvent can be used for three different biotransformation of single‐phase, biphasic, and reversed micelle systems (Tai et al., 2016). Substrates without any cosolvent were converted into control and the conversion rate was set at 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Fungal bioconversion of R‐(+)‐limonene was analysed in 100 ml Erlenmeyers flasks containing 40 ml of liquid media modified from Tai et al . (2016), with malt extract (10 g l −1 ), yeast extract (0·5 g l −1 ), bacteriological peptone (0·5 g l −1 ), glucose (10 g l −1 ), Tween 80 (0·1 g l −1 ), R‐(+)‐limonene (20 g l −1 ) and KH 2 PO 4 buffer pH 6·2. Inoculum consisted of 1 ml of spore suspension at concentration of 2 × 10 7 spores per ml re‐suspended in 0·1% Tween 80 solution, obtained from a pre‐inoculum medium of 5‐ to 7‐day‐old fungal colony.…”
Section: Methodsmentioning
confidence: 99%